THE SOCIAL ASSISTENCE FOR STUDENTS DURING THE COVID-19 PANDEMIC - Krampuža, Ilga (Education Reform: Education Content Research and Implementation Problems, 2021)
The purpose of the resarch is to exploring opportunities for students to receive social assistance from the state and local government in the conditions of the Covid-19 pandemic. Both theoretical and empirical research methods were used in this study. State social assistance to students would be expected by providing material support for the purchase of computer equipment. Municipal social assistance is expected both in the form of a crisis benefit and indirectly by supporting the student's family if it enters the status of a poor or low-income family.